Right-wing terrorism in the 21st century the 'National Socialist Underground' and the history of terror from the Far-Right in Germany - Koehler, Daniel (Routledge studies in fascism and the far right, 2017)
This book is the first comprehensive academic study of German right-wing terrorism since the early 1960s available in the English language. It offers a unique in-depth analysis of German violent, extremist right-wing movements, terrorist events, groups, networks and individuals. The book also contains a complete list of all the German right-wing terrorist groups and incidents since the Second World War. Based on the most detailed dataset of right-wing terrorism in Germany, this book offers highly valuable insights into this specific form of political violence and terrorism, which has been widely neglected in international terrorism research.